Use of complementary medicine and uptake of COVID-19 vaccination among US adults - Holger Cramer; Holger Cramer; Mirela Bilc; Mirela Bilc (Frontiers in Medicine)
This study investigated the association between complementary medicine (CM) use and the uptake of coronavirus disease 2019 (COVID-19) and flu vaccines in a nationally representative US sample. A secondary analysis of the 2022 National Health Interview Survey data indicated that, after accounting for potential confounders, overall use of CM was not a significant predictor of COVID-19 (p = 0.745) or flu vaccination uptake (p = 0.123). However, vaccination uptake was lower for both COVID-19 and flu vaccines, respectively, in individuals who visited chiropractors (AOR = 0.78, 95% CI [0.69, 0.89], p < 0.001; AOR = 0.71, 95% CI [0.63, 0.81], p < 0.001) and naturopaths (AOR = 0.66, 95% CI [0.51, 0.86], p = 0.002; AOR = 0.72, 95% CI [0.55, 0.94], p = 0.017). Uptake rates for both COVID-19 and flu vaccines were higher among individuals who visited an acupuncturist (COVID-19: AOR = 1.46, 95% CI [1.15, 1.86], p = 0.002; flu: AOR = 1.32, 95% CI [1.08, 1.63], p = 0.008). The use of mind–body medicine was associated with increased likelihood of COVID-19 vaccination uptake (AOR = 1.24, 95% CI [1.08, 1.42], p = 0.002), but not flu vaccination (p = 0.264). Visiting a massage therapist was not a significant predictor of either COVID-19 or flu vaccine uptake (p = 0.128 and p = 0.232, respectively). Overall, the pattern of associations between CM use and COVID-19 vaccination uptake was comparable to that of flu vaccination uptake.